1990
DOI: 10.1139/o90-119
|View full text |Cite
|
Sign up to set email alerts
|

Glutaraldehyde effect on hemoglobin: evidence for an ion environment modification based on electron paramagnetic resonance and Mossbauer spectroscopies

Abstract: Glutaraldehyde is a widely used reagent for hemoglobin cross-linking in blood substitutes research. However, hemoglobin polymerization by glutaraldehyde involves modifications of its functional properties, such as oxygen affinity, redox potentials, and autoxidation kinetics. The aim of this article is to investigate, by electron paramagnetic resonance and Mossbauer spectroscopies, the changes that occur in the iron environment after glutaraldehyde cross-linking. Spectrometric studies were performed with native… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 35 publications
3
8
0
Order By: Relevance
“…This result is in keeping with other studies indicating that the HBOCs have enhanced rates of transition to MetHb and ferryl heme upon exposure to H 2 O 2 (15,21). The faster rates of HBOC interaction with nitrite are also consistent with the concept that conformational constraints induced by cross-linking result in more solvent-accessible heme pockets (21,22).…”
Section: Nitrite-induced Oxidation Of Hbs In Aerobic Solutionssupporting
confidence: 91%
See 2 more Smart Citations
“…This result is in keeping with other studies indicating that the HBOCs have enhanced rates of transition to MetHb and ferryl heme upon exposure to H 2 O 2 (15,21). The faster rates of HBOC interaction with nitrite are also consistent with the concept that conformational constraints induced by cross-linking result in more solvent-accessible heme pockets (21,22).…”
Section: Nitrite-induced Oxidation Of Hbs In Aerobic Solutionssupporting
confidence: 91%
“…The rapid autoxidation of the HBOCs appears to be due to conformational constraints that make their heme pockets more open to the aqueous environment. Structural data supporting this interpretation has been acquired for glutaraldehyde-polymerized Hb (22,44). This cross-linked protein's enhanced rate of autoxidation is attributed to changes in the heme environment that decrease proximal and distal side steric hindrance and open the heme pocket toward the solvent (22).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…However, their observed behavior is in keeping with previous studies indicating that these T-state stabilized Hbs have enhanced rates of transition to metHb and ferryl heme on exposure to H 2 O 2 (5,79,81). Their faster rates of interaction with nitrite are also consistent with data suggesting that the conformational constraints induced by cross-linking result in more solvent-accessible heme pockets (5,35). The results in Table 1 also show that inorganic anions and inositol hexaphosphate (IHP), effectors that lower Hb's O 2 affinity, exert opposite effects on the rate of nitrite-induced oxidation.…”
Section: Redox Reactions Of Hb With Nitritesupporting
confidence: 89%
“…This is consistent with a Mossbauer spectroscopic study of hemoglobin that showed that the heme pocket is opened up hy polymerization [16]. As a result, polymerized hemoglobins may be more susceptible to oxidation and heme loss.…”
Section: Resultssupporting
confidence: 89%